Effects of grazing on plant species diversity and above ground biomass in a Trans- Himalayan Rangeland - Pokharel, Anita; Chhetri, Madhu; Upadhyaya, Chiranjibi P (Banko Janakari, 2007)
Limited information is available on the species composition, above ground biomass and its relations to grazing in a trans-Himalayan rangeland. Its assessment is essential for long term conservation and management. In the present study, we compared species composition, phenology, diversity index and biomass between controlled (without grazing) and open (free grazing) plots to assess the effects of grazing in the selected experimental sites of Upper Mustang during July and November 2005. Species encountered were classified as high, medium, low and non palatable and in three life form categories-grasses, shrubs and forbs. The experimental sites are dominated by forbs (80%) followed by grasses (15%) and shrubs (5%). Disturbance caused by grazing affects the phenological characteristics of the plant community. Result also reveals that species diversity, maximum possible diversity, evenness and species richness was higher in the grazed plots during July and November. A comparison of the aboveground biomass in July showed that mean percentage biomass of high, medium and low palatable species is higher in ungrazed plots. In November, the percentage biomass of only medium palatable species was higher in ungrazed plots and rest of the category is higher in grazed plots. Significant difference in July, a peak growing seasons for most of the plant species in the region reveals that the pasture has impact of livestock grazing. Keywords: Biomass, diversity, grazing effect, rangeland, species Banko Janakari: A journal of forestry information for Nepal Vol.17(1) 2007 pp.25-31